2020
DOI: 10.3389/fnhum.2020.00242
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Worsening Following DYT1 Dystonia Deep Brain Stimulation: A Multi-country Cohort

Abstract: Objective: To reveal clinical characteristics of suboptimal responses to deep brain stimulation (DBS) in a multi-country DYT1 dystonia cohort. Methods: In this multi-country multi-center retrospective study, we analyzed the clinical data of DYT1 patients who experienced suboptimal responses to DBS defined as <30% improvement in dystonia scales at the last follow-up compared with baseline. We used a literature-driven historical cohort of 112 DYT1 patients for comparison. Results: Approximately 8% of our study c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
(76 reference statements)
1
18
0
Order By: Relevance
“…Off stimulation evaluation showed worsening of dystonia, despite missing the 30% improvement threshold, thus indicating some continued benefit. All 11 patients underwent further DBS surgeries, either targeting the STN or the GPi, Additional leads did not offer meaningful improvement, if the initial leads were optimally placed (82).…”
Section: Role Of Rescue Leadsmentioning
confidence: 99%
“…Off stimulation evaluation showed worsening of dystonia, despite missing the 30% improvement threshold, thus indicating some continued benefit. All 11 patients underwent further DBS surgeries, either targeting the STN or the GPi, Additional leads did not offer meaningful improvement, if the initial leads were optimally placed (82).…”
Section: Role Of Rescue Leadsmentioning
confidence: 99%
“…Cif et al described secondary worsening after several years in a subgroup of DYT1 dystonia patients with good initial response at 12 months ( 34 ). A recent multicentre study reported secondary worsening in DYT1 dystonia after GPi DBS in 11 of 132 patients at 6 months to 3 years after DBS and was associated with younger age of onset, faster disease progression and cranial involvement ( 38 ).…”
Section: Genetic Forms Of Dystonia and Response To Gpi-dbsmentioning
confidence: 99%
“…In our present study, the pooled AER after GPi-DBS was numerically lower than that after STN-DBS, but the difference was not significant. This outcome might partly be due to the different stimulation parameters used in GPi-DBS and STN-DBS considering the stimulation-related AEs (Tsuboi et al, 2020). More studies are needed to explore the relationship between programming parameters and safety.…”
Section: The Target Of Deep Brain Stimulationmentioning
confidence: 99%